Study on the spatial variation of China’s territorial ecological space based on the standard deviation ellipse - Zhang, Yang; Jiang, Ping; Cui, Liye; Yang, Yang; Ma, Zijun; Wang, Yan; Miao, Donghui (Frontiers in Environmental Science, 2022)
In the face of the current situation of China's resource constraints, environmental degradation, and ecosystem destruction, it is necessary to thoroughly study the territorial ecological space of China and its evolution rules. Based on previous studies on the classification of ecological land use, this study proposes the concept of territorial ecological space and distinguishes it from urban space and agricultural space. A matching ecological space classification system has been established, which may help in understanding the ecosystem model and related ecological processes. According to the constructed ecological space classification system, ecological spatial data processing was conducted. The standard deviation ellipse model was used to analyze the pattern of various ecological spaces in China and the migration of their barycenter. The results of the study show the following: (1) China's territorial ecological space area showed a downward trend from 2000 to 2015. From the aspect of flow, the area of ecological space mainly flows into urban space, followed by agricultural space. According to the division of the first-level ecological space, the main ecological space structure of China is grassland ecological space and woodland ecological space. (2) The spatial distribution characteristics of China's territorial ecological space are more prominent, and the distribution is very uneven. During the study period, the variation of the standard deviation ellipse angle θ of the ecological space is small, and the migration of the barycenter is not obvious, indicating that China’s territorial ecological space is in a relatively stable state. (3) It is necessary to implement a differentiated policy on the optimization and control of territorial ecological space according to the non-equilibrium of territorial space, and build a unified and coordinated territorial space management and control system. Such a differentiation policy would provide a basis for decision making and a reference for formulating strategies for the sustainable development of the regional ecological environment and optimizing the spatial layout of the territory.